Biomimetic Architecture in Building Envelope Maintenance (A Literature) - Agus Salim, N.A.; Mydin, M.A.O; Md. Ulang, N. H. (EDP Sciences, 2014)
The study of biomimetic architecture on building envelope is the main structure of this research. The concept is believed more sustainable and efficient for energy saving, operating cost consumption, waste recycle and design renewal in the future. The inspiration from the nature developed the intention on this study to explore on what and how this concept to overcome the problems through design. Biomimicry does catch the attention of human to study more on the system and function of its nature course. The designers are not exception influenced by this concept when the form, shape, texture and colour inspired them in their design. The domination of building form will affect the building envelope as the skin of the structure. A clear impact on building failure is begun with building envelope appearance without a proper maintenance. The faults in building design place a heavy burden on the building for the rest of its operational life and there is no compensation for it. In such situations, the responsibility falls on the shoulders of the designer.